"Let's Be Careful Out There!": Learning in the world of electronic information - McDowell, Liz; Pickard, Alison (Proceedings of the International Conference on Networked Learning, 2000)
Access to information is seen as one of underpinning infrastructures and essential features of lifelong learning and is supported by government initiatives (for example DfEE, 1997). The availability of vast information resources in the electronic information world is often viewed as a positive and, indeed, liberating feature of networked learning. Claims are made that the use of electronic information enables more learner-centred approaches. If learners can undertake independent discovery and explore alternatives rather than being reliant on their teachers to provide the information they require, this provides a foundation for lifelong learning. In this paper, we aim to challenge the assumptions that access to a wealth of information will necessarily lead to the extension of learning opportunities and better learning. We draw on data from two research projects, both of which gathered data through case studies and adopted qualitative, interpretative approaches to illustrate experiences of learning, teaching and supporting learning in the electronic information world. The Higher Education study (McDowell, 2000) was an element of the IMPEL2 eLib-funded project, which undertook a set of case studies across UK HE institutions. Its purpose was to illuminate the organisational and cultural impacts associated with rapid technological and educational developments, from the perspectives of academic, library and learning support staff. The school study was based on sixteen case studies of Year 10 students in four secondary schools. It formed part of a PhD investigation of the experiences of electronic information use and learning (Pickard, 1998).